Autosomal recessive cutis laxa type-1 with complex systemic manifestations - Shruti Dhanraj Chavan; Ashish Ramchandra Deshmukh; Aniruddha Dharnidhar Gulanikar; Shilpa Satyajeet Pathrikar; Iqbal Mohammad Tariq (Wolters Kluwer Medknow Publications, 2018)
Cutis laxa (CL) is a rare connective tissue disorder characterized by loose, sagging, and redundant skin. Both inherited and acquired forms are known. A 7-year-old boy, presented with loose, sagging skin chiefly over the face, extremities, and skin folds since birth with recurrent respiratory and systemic complaints. The patient had a characteristic senile bloodhound appearance. Chest X-ray findings included emphysema, bronchopneumonia, and pulmonary hypertension. Ultrasonographic examination showed cystitis and bladder diverticula. Two-dimensional echocardiography showed primary pulmonary hypertension. Histopathological examination with Verhoeff-Van-Gieson stain showed markedly reduced elastic fibers. Serum amino acids, copper, and ceruloplasmin were normal. About sixty cases of autosomal recessive cutis laxa type 1 (ARCL-1) have been reported in literature. There is no definitive treatment available at present, and symptomatic management is the mainstay of treatment. Differential diagnosis includes Ehlers-Danlos syndrome, congenital disorders of glycosylation syndrome, and pseudoxanthoma elasticum. We report this case of ARCL-1 for its rarity and complex systemic involvement.